THE NATION’S ECONOMIC POLICIES EXPLAINED, CREATING AWARENESS TO THE PUBLIC - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 15 June 2017 - The ‘Memahami Dasar Ekonomi Negara’ briefing programme was initiated by the Ministry of Finance (MOF) Malaysia with the aim of raising the awareness of the public on the nation’s economic policies and subsidy rationalisation.